Greece's new geopolitics - Lesser, Ian O., 1957-; Larrabee, F. Stephen; Zanini, Michele; Vlachos-Dengler, Katia; Rand Corporation; International Security and Defense Policy Center; Kokkalis Foundation (Santa Monica, CA : RAND, 2001)
Greece has been profoundly affected by recent changes in the international environment, on its borders, and within the country itself. Many long-standing assumptions about Greek interests and Greece's role have fallen away and have been supplanted by new approaches. The country has become progressively more modern and more European, and its international policy has become more sophisticated. At the same time, the geopolitical scene has evolved in ways that present new challenges and new opportunities for Athens in its relations with Europe, the United States, and neighboring countries. Many of these challenges cross traditional regional boundaries and underscore Greece's potential to play a transregional role, looking outward from Europe to the Mediterranean, Eurasia, and the Middle East. This report explores the new geopolitical environment Greece faces, paying special attention to the implications for southeastern Europe and transatlantic relations; explores options for Greek strategy; and offers some new directions for policy in Greece and on both sides of the Atlantic.
Introduction -- Greece's New Strategic Environment -- Balkan Security After the Fall of Milosevic: Challenges and Implications for Greece -- The Political Economy of Infrastructure Development in and Around Southeastern Europe -- Conclusions and Policy Directions.
"National Security Research Division.
Includes bibliographical references (p. 113-123).
Also available on the internet via WWW in PDF format.
Keywords: Geopolitics -- Greece; Greece -- Foreign relations -- 1974-; Greece -- Strategic aspects